Agricultural Value Added in BRICS: A Panel Data Study - Chandrasekaran, Sharmiladevi Jekka (International Journal of Energy Economics and Policy, 2024)
Sustainable agricultural development is essential for ensuring food security, economic growth and ecological balance, which is a challenging phenomenon to achieve. This phenomenon is studied in the case of BRICS, considering agricultural value added, economic growth, openness to trade, carbon dioxide emission and net foreign direct investment. Panel unit root test, Fixed and Random Effect Model, Panel Cointegration test and Panel Causality are studied. Results of the analysis indicate that in all the BRICS countries, agricultural value added is significant to economic growth, inward foreign direct investment is reduced with agricultural growth, and inward foreign direct investment causes trade openness.